2018
DOI: 10.1016/j.apsb.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of polyvinylpyrrolidone/paclitaxel self-assemblies for breast cancer

Abstract: The goal of this investigation was to develop and demonstrate a polymer/paclitaxel self-assembly (PTX-SA) formulation. Polymer/PTX-SAs were screened based on smaller size of formulation using dynamic light scattering analysis. Additionally, fluorescence microscopy and flow cytometry studies exhibited that polyvinylpyrrolidone (PVP)-based PTX-SAs (PVP/PTX-SAs) had superior cellular internalization capability in MCF7 and MDA-MB-231 breast cancer cells. The optimized PVP/PTX-SAs exhibited less toxicity to human r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…A semi-quantitative cellular uptake assay of TA-LF complexes was examined by flow cytometry and fluorescence microscopy methods. To allow cellular uptake quantification, TA-LF assemblies were labeled with coumarin-6 using our previously reported method [ 24 , 25 ]. The extent of dye internalized was used to track uptake of TA-LF self-assemblies into cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A semi-quantitative cellular uptake assay of TA-LF complexes was examined by flow cytometry and fluorescence microscopy methods. To allow cellular uptake quantification, TA-LF assemblies were labeled with coumarin-6 using our previously reported method [ 24 , 25 ]. The extent of dye internalized was used to track uptake of TA-LF self-assemblies into cells.…”
Section: Methodsmentioning
confidence: 99%
“…The drugs (gemcitabine, carboplatin, irinotecan) encapsulated in TA-LF formulations were prepared following our established protocol [ 24 ]. Their anti-cancer efficacies were evaluated using a colorimetric cell titer 96 aqueous one solution cell proliferation assay (MTS assay, Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This effect lacked interaction with the immune system. [ 130 ] In particular, Ishihara et al. demonstrated that the coating of nanoparticles with PVP polymer increased their half‐life and, at the same time, prevented the induction of the ABC phenomenon.…”
Section: Strategies To Overcome Side Effects Of Pegmentioning
confidence: 99%
“…At 70% confluence, cells were exposed to 10 and 20 µM TA for 24 h along with the untreated control. The cells (both dead and live) were pelleted, lysed, and processed for protein profiling studies [72][73][74][75][76][77] . After TA treatment, cell lysates were prepared using CelLytic M lysis buffer (sigma Aldrich, St. Louis, MO, USA).…”
Section: Determination Of Intracellular Reactive Oxygen Species (Ros)mentioning
confidence: 99%